ORGANIZATION OF ULTRASOUND EXAMINATION IN GYNECOLOGICAL CANCER PATIENTS IN KURSK REGION - E. A. Podolskaya (Опухоли женской репродуктивной системы, 2017)
Objective: to analyze organizational aspects in the work of ultrasound diagnostic services of Kursk city and Kursk region in terms of cancer patients’ primary examination, specialized treatment, follow-up and seeking medical care in private clinics by these patients.Materials and methods. The study included 245 patients followed-up in the Kursk Regional Clinical Oncology Dispensary during 2012–2015. We analyzed the reports of ultrasound examination (USE) performed by various healthcare institutions at different stages of diagnostics, treatment and follow-up. We also assessed the quality and completeness of USE as well as the frequency of seeking medical assistance at private clinics.Results and conclusions. We revealed substantial organizational problems in USE of gynecological cancer patients in Kursk region.